2007
DOI: 10.1248/jhs.53.734
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and Antilipidperoxidative Effects of a Polyherbal Formulation, Diakyur, in Experimental Animal Models

Abstract: The present study investigates the effect of Diakyur, a polyherbal formulation composed of powder of Cassia javanica and dried, standardised aqueous extracts of Cassia auriculata, Salacia reticulata, Gymnema sylvestre, Mucuna pruriens, Syzygium jambolanum, Terminalia arjuna on blood glucose level of normal and diabetic animals as well as lipid peroxide level in normal and 28 day drug treated diabetic rats. The raw materials and the formulation were standardised by high performance thin layer chromatography (HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The probable mechanism of action of the fractions is due to their Advanced molecular studies showed that methanol extract of black jamun plant modulate the expression of glucose transporter (Glut-4), peroxisome proliferator activator receptor gamma (PPARc) and phosphatidylinositol-3-kinase (PI3 kinase) comparable with insulin and rosiglitazone (Anandharajan et al 2006). Evaluation of black jamun containing antidiabetic poly herbal formulation in alloxan induced diabetic rats also showed significant hypoglycemic activity, positive glucose tolerance activity and reduced lipid peroxidation in various organs compared to that of the diabetic control animals (Joshi et al 2007). Meshram et al (2011) studied on hypoglycaemic action of black jamun seeds and concluded that the methanol extracts of black jamun seeds may act in a variety of diabetic conditions with or without functioning of pancreatic b-cells.…”
Section: Antidiabetic Activity From Fruit Part Extracts Of Black Jamumentioning
confidence: 99%
“…The probable mechanism of action of the fractions is due to their Advanced molecular studies showed that methanol extract of black jamun plant modulate the expression of glucose transporter (Glut-4), peroxisome proliferator activator receptor gamma (PPARc) and phosphatidylinositol-3-kinase (PI3 kinase) comparable with insulin and rosiglitazone (Anandharajan et al 2006). Evaluation of black jamun containing antidiabetic poly herbal formulation in alloxan induced diabetic rats also showed significant hypoglycemic activity, positive glucose tolerance activity and reduced lipid peroxidation in various organs compared to that of the diabetic control animals (Joshi et al 2007). Meshram et al (2011) studied on hypoglycaemic action of black jamun seeds and concluded that the methanol extracts of black jamun seeds may act in a variety of diabetic conditions with or without functioning of pancreatic b-cells.…”
Section: Antidiabetic Activity From Fruit Part Extracts Of Black Jamumentioning
confidence: 99%
“…This product may have a wide spectrum of biological functions. Furthermore, these polyherbal products may produce synergetic action due to multiple ingredients and contain potentially agonistic/antagonistic pharmacological agents within themselves 7 . The study by Mahajan et al showed the polyherbal of C. caesia, E. alsinoide, C. lanatus, G. sylvestre and T. cordifolia, W coagulans, and C bonduct antidiabetic effect to rats induced by alloxan at 400 mg/kg of body weight.…”
Section: Discussionmentioning
confidence: 99%
“…So, concluded that Diakyur at a dose of 1600 mg/kg p.o is safe for long term treatment in diabetic condition. 33 Diasulin A polyherbal formulation containing Cassia auriculata, Coccinia indica, Curcuma longa, Emblica officinalis, Gymnema sylvestre, Momordica charantia, Scoparia dulcis, Syzygium cumini, Tinospora cordifolia, Trigonella foenum graecum Previous Investigation suggest that controls the blood glucose level by increasing glycolysis and decreasing gluconeogenesis with a lower demand of pancreatic insulin than in untreated rats. This is possible, because it regulates the activities of hepatic glucose metabolic enzymes.…”
Section: Diabridmentioning
confidence: 99%